Enhancing Clear Radiance Generation for Geostationary Hyperspectral Infrared Sounder Using High Temporal Resolution Information - Di Di; Jun Li; Zhenglong Li; Jing Zheng; Xinya Gong (Geophysical Research Letters)
Abstract With high spatio‐temporal resolution geostationary hyperspectral infrared sounder (GeoHIS) observations, monitoring, and predicting rapidly changing weather events are expected to be improved with continuous information of 3D weather cube. However, due to the nature of radiation, clouds prevent an adequate retrieval of atmospheric thermodynamic information under clear‐sky conditions due to large uncertainties in the current radiative transfer model. Removing cloud effects from GeoHIS sub‐footprint is an alternative approach for enhancing clear radiance generation. Such cloud removal can be achieved through the optimal cloud‐clearing (OCC) method, which usually relies on the assumption of atmospheric spatial homogeneity. With high temporal resolution observations from GeoHIS, cloud removal can also be achieved through OCC but using the assumption of temporal homogeneity. This concept was demonstrated using 15‐min Geostationary Interferometric Infrared Sounder (GIIRS) observations. The longwave GIIRS clear radiances under partially cloud cover can be effectively produced with observation errors less than 0.02 ± 0.86 K and 0.04 ± 0.77 K for 11 and 12 μm, respectively.